Pengaruh Profitabilitas dan Pengungkapan Tanggung Jawab Sosial Terhadap Nilai Perusahaan - Triyana Triyana; Sri Ayem (CV. Syntax Corporation Indonesia, 2021)
Sustainable development according to Law No. 32 of 2009 on Environmental Protection and Management (UU PPLH), is development that meets the demands of the present without sacrificing the potential of future generations. Since the enactment of Law No. 40 of 2007, Article 74 paragraph 1, the disclosure of social responsibility is no longer an option but a necessary attitude. The more environmental responsibilities businesses take on, the better their public image. The study aims to examine empirical evidence on whether profitability has an effect on a company's value. Disclosure of social responsibility has an effect on a company's value. Profitability and disclosure of social responsibility simultaneously affect the value of the company. Mass communication media will be able to weaken or actually strengthen the relationship between profitability and corporate value. Mass communication media will be able to strengthen or weaken the relationship between social responsibility and corporate values. The study used secondary data, the annual report of cement companies with a research population of 30 companies. The sampling technique used is a purposive sampling technique. This sample numbered 6 companies, the data analysis method was carried out using simple regression, multiple linear regression analysis and regression analysis of absolute value difference tests. The results showed that profitability partly had a positive and insignificant effect on the value of the company. Corporate social responsibility has a positive effect on the value of the company. Profitability and corporate social responsibility together or simultaneously affect the value of the company. Mass communication media weakens the relationship between profitability and corporate value. Mass communication media weakens a company's social responsibility relationship with corporate values